Molecular Targets in Metastatic Colorectal Cancer: A Review - Colombo, Alfredo; Porretto, Concetta Maria (Indian Journal of Medical and Paediatric Oncology, 2025)
In recent years, the molecular and genetic features of colorectal cancer (CRC) have been used to categorize the disease, which has made it possible to develop therapeutic approaches based on predictive biomarkers. Valuable drivers for individualized treatment plans are biomarkers including NTRK fusions, RAS and BRAF mutations, HER2 amplification, and microsatellite instability (MSI). Furthermore, the regular use of molecular predictive diagnostics, including liquid biopsies and the reintroduction of anti-epidermal growth factor receptor (EGFR) monoclonal antibodies, presents new opportunities for the therapeutic management of patients with CRC. With an emphasis on recent developments in EGFR blockade and novel biomarkers (MSI, HER2, and NTRK), we have provided an overview of the state of targeted therapy for patients with metastatic CRC in this review.
Keywords: colon; neoplasm; Ras; Braf; ctDNA